[Re] Introducing the Concept 'Intra-Local Governmental Relations' for Proper and Future Usage in Public Administration Research and Education: A Possible Case for Bathos - Arthur Shopola; Ricky Mukonza (Camarines Sur Polytechnic Colleges, 2023)
Usage of the phrase 'conceptual bathos' in this paper is simply to engender curiosity of the readership but above that, it is used to caution emerging researchers [especially in the field of public administration] against overlooking or demeaning important subjects or concepts to simple or ordinary ones. Specifically, the paper refers to 'Intra-local governmental relations' as a concept that has suffered the same cause of negation to argue for its proper usage in future. This concept is found within the orbit of intergovernmental relations (IGR) and is a term of reference for various internal municipality relations. However, it is suspected that because of the inherent similarities and motherhood relationship between IGR and ILGR researchers have failed to draw differences thereby causing confusion. The extent of this confusion may lead to a suggestion that these concepts are inseparable and therefore can be used to explain each one's context. The current paper characterises such acts as tangential and generalist conceptual approach which is often not aware of the important groupings (classifications) of governmental relations.  By collecting and unpacking data from the existing research outputs, books, journal articles and government publications, the current paper finally realised its objective, which was to re-introduce ILGR into the academic discourse and the anticipation is that emerging Public Administration researchers and scholars will use the concept properly and correctly.